Glide performance analysis of underwater glider with sweep wings inspired by swift - Wang, Yanhui; Wang, Cheng; Yang, Ming; Liang, Yan; Han, Wei; Yang, Shaoqiong (Frontiers in Marine Science, 2022)
Underwater glider (UG) is one of the most promising autonomous observation platforms for long-term ocean observation, which can glide through seawater columns by adjusting its buoyancy and attitude. Hydrodynamic shape, especially the wing parameters, has an important influence on the glide performance of UG. In this paper, a sweep wing strategy inspired by the swift wings is proposed to apply pre-adjustable sweep wings for UGs, so as to improve the glide performance in different glide conditions. The approximate model that describes the relationship between the hydrodynamic coefficients of UG and the wing sweep angles is established with computational fluid dynamics method. By importing the approximate models into the dynamic model, the glide performance analysis, including endurance ability and trajectory accuracy, is performed to analyze the effect of the various sweep wings. The analysis results indicate that different sweep angles of wings are required by UG to obtain the optimal ability in gliding range, gliding duration, turn and resisting current, and the sweep wing strategy is useful for UG to improve its performance in observation mission due to the uncertainty of ocean environment.